Plasma binding proteins for platelet-derived growth factor that inhibit its binding to cell-surface receptors. - Raines, E W (1984)
Evidence is presented that the binding of platelet-derived growth factor (PDGF) to plasma constituents inhibits the binding of PDGF to its cell-surface mitogen receptor. Approximately equivalent amounts of PDGF-binding activity were found in plasma from a number of different species known by radioreceptor assay to contain PDGF homologues in their clotted blood. Activation of the coagulation cascade did not significantly alter the PDGF-binding activity of the plasma components. Three molecular weight classes of plasma fractions that inhibit PDGF binding to its cell-surface receptor were defined by gel filtration: approximately equal to 40,000, 150,000, and greater than 500,000. Specific binding of 125I-labeled PDGF to the highest molecular weight plasma fraction could also be demonstrated by gel filtration. The binding of PDGF to these plasma components was reversible under conditions of low pH or with guanidine X HCl, and active PDGF could be recovered from the higher molecular weight fractions. Immunologic and functional evidence is presented that the highest molecular weight plasma fraction may be alpha 2-macroglobulin. A model is proposed in which the activity of PDGF released in vivo may be regulated by association with these plasma binding components and by high-affinity binding to cell-surface PDGF receptors.